Getting magnetocaloric materials into good shape: Cold-working of La(Fe, Co, Si)13 by powder-in-tube-processing. (September 2018) - Funk, Alexander; Freudenberger, Jens; Waske, Anja; Krautz, Maria
Abstract: The powder-in-tube (PIT) technology was applied to La(Fe, Co, Si)13 powder cladded by a thin seamless austenitic steel jacket. Wires appear to be promising in the search for alternative regenerator geometries, since they offer various possibilities of arrangements allowing to optimise heat transfer and pressure loss within the boundaries set by parallel plate and sphere beds. Here, pre-alloyed La(Fe, Co, Si)13 powder was filled in a AISI 316L austenitic steel tube and swaged to wires with an outer diameter of 1 mm. By mechanical deformation, the steel jacket thickness was reduced to about 100 μm surrounding the magnetocaloric core. A post-annealing of only 10 min at 1050 °C is sufficient to form the magnetocaloric NaZn13 -type phase resulting in an entropy change close to the value of a pure reference sample. The presented technology is not limited to La(Fe, Co, Si)13 /steel combination but can be extended to material pairs involving wire core materials with a first order transition, such as Fe2 P-type or Heusler alloys. Graphical abstract: Shaping process of brittle magnetocaloric materials for room-temperature application: A steel tube is filled with pre-alloyed compacted powder and swaged down to 1 mm composite wires ready to assemble in a magnetocaloric regenerator after heat treatment. Image 1 Highlights: Magnetocaloric wires with thin steel jacket were produced by cold-working. The amount of magnetocaloric material is about 58 vol% in the wire. Cold working results in refined microstructure and hence reduced annealing time. The wires can be readily assembled in a magnetocaloric regenerator.